The history of the greek catholic eparchy of Mukachevo in 1848–1849 - Molnár Ferenc; Молнар Федір; Molnar Fedir (My University, 2023)
Abstract. The article addresses the problem of role of the Greek Catholic Eparchy of Mukachevo in the Hungarian Revolution and War of Independence of 1848–1849. Considerable attention is paid to analyze the religious and political activity of Bishop Vasyl Popovych of Mukachevo. The author highlights that the spring events of 1848 created a new situation in Hungary. First in the history of the country a government accountable to the legislation was formed, whose first measures included the abolishment of serfdom. The so-called «April Laws» of 1848 sanctioned by Ferdinand V, the Habsburg king of Hungary had a great influence on the feudal system. The last Diet of Reform Era adopted laws, which paved a way for the bourgeois transformation of the country. It is alleged that one of the most important issues was the determination of the relationship between church and state in spring 1848. This time, the relationship between the Batthyány Goverment and the leaders of the Catholic Church of Hungary was not free from difficulties. The Catholic Church has lost its state religion status. The history of the Eparchy of Mukachevo in the revolutionary events of 1848–1849 is one of the less researched issues. On the basis of analysis of the review of archival sources and historiography of the topic, it is established that the Eparchy of Mukachevo played an exceptional role in support of hinterland of the Hungarian War of Independence. As noted, it had jurisdiction over seven counties in Northeastern Hungary (Zemplin, Ung, Bereg, Ugocha, Sotmar, Sabolch and Maramorosh) and the Hajdú District populated by Rusyn-, Hungarian- and Romanian-speaking believers. Thus, the Greek Catholic clergy had a strategic role to ensure peace between the different peoples. The author comes to the conclusion that Bishop Vasyl Popovych and his prelacy trusted in the goodwill of the Hungarian liberal leaders. The bishop focused on the interests of his eparchy in all circumstances. The years of 1848–1849 were abundant in political and military turns. Popovych was always far from any form of extremism, calmness and prudence controlled his actions. In the end, it is revealed that the Greek Catholic clergy believed: the Hungarian government wanted to create a country, where the Byzantine rite community gets into a favourable, more honoured position.

Резюме. Розглянуто роль Мукачівської греко-католицької єпархії у подіях Угорської революції та визвольної боротьби 1848–1849 рр. Значну увагу приділено аналізу релігійної і політичної діяльності Мукачівського єпископа Василя Поповича. Зазначено, що весняні події 1848 р. в Угорщині привели до нової суспільно-політичної ситуації. Констатовано, що вперше в історії країни було сформовано підпорядкований законодавчий орган уряду, серед нагайних заходів якого – ліквідація інституту кріпацтва. Стверджено, що схвалені королем Фердинандом V «квітневі закони» похитнули саму основу феодального ладу, а останні Державні збори епохи реформ розробили таке законодавство, яке відкрило шлях до буржуазних перетворень у країні. Стверджено, що oдним із найсуттєвіших питань весни 1848 р. залишалося визначення формату відносин між державою та Церквою; відносини між урядом Баттяні та Католицькою Церквою не були безпроблемними – католицизм утратив статус державної релігії. Зауважено, що історія Мукачівської греко-католицької єпархії у 1848–1849 рр. належить до малодосліджених тем. На основі аналізу історіографії й архівних джерел встановлено, що Мукачівська єпархія відігравала унікальну роль у забезпеченні тилу визвольної боротьби Угорщини. Зазначено, що вона охоплювала територію семи комітатів (Земплін, Унг, Берег, Угоча, Сотмар, Саболч та Мараморош) і Гайдуцького округу, де проживало підпорядковане їй русько-українське, угорське та румунське населення. Констатовано, що греко-католицьке духовенство відігравало стратегічну роль у забезпеченні міжнаціонального миру в регіоні. Виснувано, що єпископ В. Попович і його оточення також вірили в добрі наміри угорських лібералів, а перед нами вимальовується образ єпископа, який за будь-яких обставин захищав передовсім інтереси своєї єпархії. Спостережено, що 1848–1849 рр. були багаті на політичні й військові повороти, В. Попович завжди був далеким від будь-яких виявів крайнього радикалізму, для його вчинків притаманні самовладання та обдуманість. На закінчення розкрито побоювання греко-католицького духовенства: угорська влада хоче створити таку державу, у якій громада візантійського обряду матиме сприятливіші ніж раніше умови існування.
Історія Мукачівської греко-католицької єпархії у 1848–1849 роках
Keywords: Greek Catholic Eparchy of Mukachevo; Bishop Vasyl Popovych; Northeastern Hungary; Lajos Kossuth; Catholic Church of Hungary